GRAMMATICAL COMPARATIVE ANALYSIS OF THE MAIN GRAMMATICAL CATEGORIES IN ENGLISH AND UZBEKISTAN - Jamoliddinova Yosuman; Allayev Zafar Mengboyevich (International Journal of Literature and Language Studies, 2026)
Abstract: This article provides a comparative analysis of the main grammatical categories in English and Uzbek. During the study, the grammatical structure, morphological and syntactic features, word classes, specific aspects of the categories of number, case, tense, mood, proportion and person of both languages are studied from a scientific point of view. Also, the differences and similarities between the analytical features of the English language and the agglutinative nature of the Uzbek language are highlighted. The study analyzes the formation, use and communicative functions of grammatical categories based on the comparative method. The results of the article serve to provide a deeper understanding of the grammatical systems of English and Uzbek, improve the methodology of teaching foreign languages, and develop scientific research in the field of translation studies. As a result of the study, common and different aspects of the grammatical systems of the two languages are identified and their linguistic significance is substantiated.